Struktur Organisasi Sebagai Instrumen Penguatan Tata Kelola Lembaga Pendidikan Yang Efektif - Abdullah Muis Kasim; Paulin Alfantina Nelci; Theresia Bunga Karlince; Yeremia Aristania Meti; Maria Ica Siming; Marhaban Sahrir Ramadhan Kau (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze organizational structure as an instrument for strengthening effective educational institution governance. The research uses a qualitative descriptive approach through library research. Data were collected from various scientific literature such as books, journals, and relevant government regulations related to educational management. The results show that organizational structure plays an important role in creating clarity of duties, authority, and responsibilities within educational institutions. A clear organizational structure is proven to improve coordination effectiveness, accelerate decision-making processes, and strengthen the principles of accountability, transparency, effectiveness, and efficiency in educational governance. In addition, the study also finds that weak organizational structure may lead to task overlap and low work effectiveness. Therefore, organizational structure is a strategic element in achieving professional and high-quality educational governance.